Symbolic Violence and the Use of the Evangelical Religion at the Counter-Subversive war in Guatemala - Sáenz Bonilla, Juan Pablo (2025)
This article examines two ways in which the Guatemalan state and army exercised symbolic violence during the counter-subversive war of the 1980s. Specifically, it discusses the self-presentation strategies (and those of its enemies) used by these political institutions, as well as the use of religion and evangelical churches as symbolic weapons. With this, it becomes evident that, in addition to the physical violence typical of the war, symbolic violence was exercised, both against the Guatemalan community in general (defined as outside symbolic violence) and within the Army itself (defined as inside symbolic violence). The conclusions are drawn from the review of official documents and previous specialized research on the subject, as well as from the interpretation based on the theory of the sociologist Pierre Bourdieu.